2021
DOI: 10.1002/anie.202017234
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the Unprecedented Stereochemistry of an Enzymatic Nitrile Synthesis through a Combined Computational and Experimental Approach

Abstract: In this contribution, the unique and unprecedented stereochemical phenomenon of an aldoxime dehydratase‐catalyzed enantioselective dehydration of racemic E‐ and Z‐aldoximes with selective formation of both enantiomeric forms of a chiral nitrile is rationalized by means of molecular modelling, comprising in silico mutations and docking studies. This theoretical investigation gave detailed insight into why with the same enzyme the use of racemic E‐ and Z‐aldoximes leads to opposite forms of the chiral nitrile. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…As an enzyme for this initial docking study, we chose the aldoxime dehydratase from Rhodococcus erythropolis (OxdRE) since crystal structures are available for this enzyme (PDB 3a15, 3a16, 3a17) [24] , and based on these data we previously could successfully design mutants in a molecular modeling study for the synthesis of chiral nitriles using the software MOE. [25] Due to the availability of this suitable docking model based on MOE, [26] which also has been proven to be a powerful tool in several other works, [27,28] we used this software MOE again for the current study (Figure 2). Interestingly the docking study revealed that the fatty aldoximes do not need to be fully incorporated in the active site.…”
Section: Resultsmentioning
confidence: 99%
“…As an enzyme for this initial docking study, we chose the aldoxime dehydratase from Rhodococcus erythropolis (OxdRE) since crystal structures are available for this enzyme (PDB 3a15, 3a16, 3a17) [24] , and based on these data we previously could successfully design mutants in a molecular modeling study for the synthesis of chiral nitriles using the software MOE. [25] Due to the availability of this suitable docking model based on MOE, [26] which also has been proven to be a powerful tool in several other works, [27,28] we used this software MOE again for the current study (Figure 2). Interestingly the docking study revealed that the fatty aldoximes do not need to be fully incorporated in the active site.…”
Section: Resultsmentioning
confidence: 99%
“…245 Protein engineering, culture condition optimization, and chemo-enzymatic cascade of characterized aldoxime dehydratases are in fast growing development, and more exciting progresses can be expected. 246,247…”
Section: Discussionmentioning
confidence: 99%
“…245 Protein engineering, culture condition optimization, and chemo-enzymatic cascade of characterized aldoxime dehydratases are in fast growing development, and more exciting progresses can be expected. 246,247 9 Author contributions Mingyu Liu: investigation, visualization, and writingoriginal dra; Shengying Li: conceptualization, funding acquisition, and writingreview & editing.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, it has been reported that ipso -hydroxylation and subsequent fragmentation are unusual microbial pathways to degrade sulfonamide antibiotics in the environment, but until now there is no research focusing on whether this emerging fragmentation pathway of sulfonamide antibiotics exists in human metabolism. Recent decades have witnessed the increasing connection between computational and experimental chemistry to solve a wide array of enzyme-catalyzed reaction mechanisms. , The present work illustrates a highly promising synergistic interplay between experiments and computations working toward metabolic mechanisms of sulfonamide antibiotics, with a focus on sulfamethoxazole (SMX) metabolism catalyzed by human CYP450 enzymes as SMX is one of the most widely applied sulfonamide antibiotics for the treatment of urinary tract infections, bronchitis, and prostatitis for human beings and is becoming a ubiquitous pollutant in the environment . Moreover, some other widely applied sulfonamide antibiotics are studied as well to confirm if the metabolic profiles obtained by SMX is universal or not, including sulphadoxine, sulfadimethoxine, sulfapyridine, sulphamerazine, sulphabromomethazine, sulphameter, sulphachloropyrazine, and sulphadimethoxine.…”
Section: Introductionmentioning
confidence: 91%